Brujería capitalista y turistas pishtaco: Tensiones ocultas en torno al turismo de ayahuasca entre los shipibo de San Francisco (Amazonia peruana) - Slaghenauffi, Doriane Sabine (Pontificia Universidad Católica del Perú, 2025)
The emergence of “shamanic tourism” in some Shipibo-Konibo villages and urban areas has led to a recrudescence of vernacular witchcraft practices, now integrated into the new sociological context of the commercialization of local vegetalist shamanism. This has brought about sorcery attacks both on rival shamans and on tourists seeking a shamanic and hallucinogenic experience, some of whom in turn become the target of sorcery rumors. These occult practices and interpretations can be seen, on the one hand, as forms of resilience adopted by Shipibo shamans in order to cope with and benefit from the current context of transition to capitalism, which is increasingly present within the communities, and, on the other hand, as manifestations of frustration and anxiety about the recuperation of local shamanism by global culture, symptomatic of the traditionally ambiguous links between gringos and Native Amazonians.

La aparición del «turismo chamánico» en algunas comunidades y zonas urbanas shipibo-konibo ha provocado un incremento de las prácticas brujeras vernáculas, ahora integradas en el nuevo contexto sociológico de la comercialización del chamanismo vegetalista local. Este clima provoca ataques de brujería tanto a los chamanes rivales como a los turistas que buscan una experiencia chamánica y alucinógena, algunos de los cuales se convierten a su vez en objeto de rumores de brujería. Estas prácticas e interpretaciones ocultas son tanto formas de resiliencia construidas por los chamanes shipibo para afrontar y beneficiarse del actual contexto de transición al capitalismo, cada vez más presente en las comunidades, como manifestaciones de frustración y ansiedad ante la recuperación del chamanismo local por parte de la cultura global, sintomática de los vínculos tradicionalmente ambiguos entre kirinko (extranjeros) e indígenas.
Capitalist Witchcraft and Pishtaco Tourists: Occult Tensions Around Ayahuasca Tourism Among the Shipibo of San Francisco (Peruvian Amazon)
Keywords: Shipibo-Konibo; Peruvian Amazon; Shamanic tourism; Vegetalism; Witchcraft; Ayahuasca; Shipibo-Konibo; Amazonía peruana; Turismo chamánico; Vegetalismo; Brujería; Ayahuasca; https://purl.org/pe-repo/ocde/ford#5.04.03